PENERIMAAN DIRI: STUDI FENOMENOLOGI PADA GURU ABK - Aulia Rakhmah; Fikrie (Berajah Journal, 2023)
Self-acceptance is the ability to embrace both one's strengths and weaknesses. Special schools are formal educational institutions designed for specific participants, catering to children with special needs. This research aims to identify the factors influencing self-acceptance among special education teachers (SETs). The research methodology used is qualitative research with a phenomenological design. The study involved three participants who possess the characteristics of SETs and exhibit good self-acceptance. Data collection techniques used were semi-structured interviews and non-participant-overt-naturalistic observation. The results indicate that SETs' self-acceptance is influenced by self-understanding, realistic expectations, favorable attitudes of society members, absence of severe emotional disturbances, influence of past success experiences, identification with individuals displaying good self-adjustment, stable self-concept, and additional factors such as age maturity that can affect self-acceptance among SETs.